2021
DOI: 10.1002/icd.2230
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of children's experience and expression of pride

Abstract: To understand socialization pathways in the development of specific, self‐relevant emotions, we examined the socialization of third‐grade children's experience and expression of pride in a sample of 196 mother–child dyads, including children's gender and race as instantiations of cultural contexts. Mothers' self‐reported beliefs about the value of positive emotions, beliefs about the value of negative emotions, and positive expressivity within the family were examined in relation to Black and White boys' and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Likewise, embarrassment centers on the commission of an accidental, yet socially unacceptable action (in this case, spilling food on one’s shirt; Keltner & Buswell, 1997; Lewis, 2016). Conversely, lower attention directed to the referent for pride may reflect parents’ desire to promote humility (see Hagan et al, 2021) and avoid hubris.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, embarrassment centers on the commission of an accidental, yet socially unacceptable action (in this case, spilling food on one’s shirt; Keltner & Buswell, 1997; Lewis, 2016). Conversely, lower attention directed to the referent for pride may reflect parents’ desire to promote humility (see Hagan et al, 2021) and avoid hubris.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study involving third-grade children (mostly 8 years of age) and their mothers, it was found that children's sense of pride, a positive self-evaluative emotion, was fostered by mothers who placed a high priority on experiencing and expressing positive emotion. On the other hand, children whose mothers were more likely to emphasize negative emotions inhibited pride in their children (Hagan et al, 2021). Socialization influences the extent to which children assimilate a culture's norms, beliefs, and values.…”
Section: Cultural Variation In Child Socializationmentioning
confidence: 99%